2012
DOI: 10.1007/s00213-012-2715-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of nicotinic acetylcholine receptors in the effects of cocaine-paired contextual stimuli on impulsive decision making in rats

Abstract: Rationale Chronic cocaine exposure produces unconditioned enhancement in impulsive decision making; however, little is known about the effects of cocaine-paired conditioned stimuli on this behavior. Thus, this study explored the effects of cocaine-paired contextual stimuli on impulsive decision making and the contribution of nicotinic acetylcholine receptors (nAChRs) to this phenomenon. Methods Rats were trained to achieve stable performance on a delay discounting task, which involved lever press-based choic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…That said, drugassociated situational cues are known to alter DA system activity (Duvauchelle et al, 2000;Weitemier and Murphy, 2009) and expression of voluntary reward-seeking actions (Ostlund et al, 2010;Xie et al, 2012), and this raises the possibility that cocaine-induced learning contributed to the effects described here. However, rats in the current study were administered cocaine in the chambers used for initial training, but were retrained and tested in a distinct chamber (used for FSCV recordings) that was never directly associated with cocaine.…”
Section: Discussionmentioning
confidence: 96%
“…That said, drugassociated situational cues are known to alter DA system activity (Duvauchelle et al, 2000;Weitemier and Murphy, 2009) and expression of voluntary reward-seeking actions (Ostlund et al, 2010;Xie et al, 2012), and this raises the possibility that cocaine-induced learning contributed to the effects described here. However, rats in the current study were administered cocaine in the chambers used for initial training, but were retrained and tested in a distinct chamber (used for FSCV recordings) that was never directly associated with cocaine.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, context-mediated learning has been shown to play an important role in other forms of behavioral sensitization [76]–[78]. Furthermore, a recent study found that cocaine-paired contextual stimuli can provoke impulsive decision making in rats [79]. We have also recently shown that contextual cues paired with alcohol intoxication produce a transient disruption in instrumental control, causing rats to shift from goal-directed to habitual performance [31].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is limited evidence from studies in rodents and humans that pharmacological modulation of nicotinic acetylcholine receptors (nAChRs) can shift choice preference in tasks that assess cost benefit decision making (Mitchell, 2004; Reynolds et al, 2004; Dallery and Locey, 2005; Kolokotroni et al, 2011; Mendez et al, 2012; Xie et al, 2012). Finally, cholinergic signaling has been implicated in the etiology and/or treatment of numerous neuropsychiatric conditions in which cost benefit decision making is altered, including schizophrenia, Alzheimer’s disease, attention deficit hyperactivity disorder (ADHD), Parkinson’s disease, and addiction (Clark and Robbins, 2002; Kalivas and Volkow, 2005; Karlawish et al, 2005; Thompson et al, 2007; Williams and Adinoff, 2008; Euteneuer et al, 2009; Weiler et al, 2009;Gleichgerrcht et al, 2010).…”
Section: Introductionmentioning
confidence: 99%